Cinema consumption in Colombia: an economic approach - Espinal-Monsalve, Nora Elena; Ramos-Ramírez, Andrey David; Balbín-Espinal, Isabel Cristina; Echavarría-Carvajal, Jorge (Sociedad y Economía, 2020)
This article analyzes the determinants of attendance and frequency of assistance to cinema in Colombia. Using the data from the 2014 Cultural Consumption Survey, Heckman selection models are estimated to detect and correct selection biases that may arise in the research problem. The results indicate that although this activity is part of a model of mass cultural consumption, cultural capital and income, they remain important determinants in the consumption decisions of individuals. Factors such as age, marital status and occupation were also relevant. This work contributes to the applied literature in the country, to the extent that it allows a broader behavioral knowledge of the cinema consumer.